LEVEL AND DYNAMICS OF PARTIAL PRODUCTIVITY AS INDICATORS OF COMPETITIVENESS IN AGRICULTURE - Marković, Katarina (Economics of Agriculture, 2009)
As one of the factors of success, competitiveness is measured in all sectors of economy and also in agriculture. Level of competitiveness of agriculture on domestic and world market can be quantified by using different methodology. As indicators of competitiveness of agriculture in this paper are used level and dynamic of partial productivity – labour productivity and land productivity. Food and Agriculture Organization (FAO) statistical data was source for estimating those indicators. Labour productivity and land productivity are measured for Serbian agriculture and agriculture in different countries in European Union.